Dehumanization of Women by Da'iyah (Media Contest in Religious Lectures) - Nurun Najwah (Jurnal Living Hadis, 2022)
The dehumanization of women in the religious framework in the media is in the form of defining women as "free" human beings. The narrative is strongly framed because it is socialized by the da'i (male) and the da'iyah. There have not been many studies that have paid attention to the substance of religion, how the da'iyah (women preachers) are actively and massively involved in delivering their da'wah material which translates women, not as creatures that need to be humanized based on religious doctrine through the lectures of three da'iyah Mamah Dedeh (Dedeh Rosdiana); dr. Aisyah Dahlan and Dr. Oki Setiana Dewi through the youtube channel in six contents. Three questions were posed: (1) How are (religious) values ​​regarding the dehumanization of women presented in religious lectures in the media; (2) How is the role of da'iyah in influencing the dehumanization of women; (3) How is the media contestation in religious lectures that do not humanize women. Misinterpretations in the form of dehumanization of women by the da'iyah are generally caused by a literal, partial, and superficial reading of religious doctrines. Therefore, although it is realized that the ideology of the media is never in line with religious values ​​that are humanist and full of moral messages, religious lectures in the media need to be studied carefully, so that religious messages that are "more humane for women" through the media are not denied.